PENGARUH KEMAMPUAN KERJA, BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA (STUDI KASUS PADA KARYAWAN PUSKESMAS DI KECAMATAN KRANGGAN, KABUPATEN TEMANGGUNG) - Christine Gita Anggraeni; Widarta Widarta (JURNAL LENTERA BISNIS, 2023)
This study aims to analyze the effect of work ability, organizational culture, and work discipline on the performance of Public Health Center employees in Kranggan District, Temanggung Regency. This type of research is a quantitative descriptive research. Data collection techniques used through the distribution of questionnaires and interviews. The sample used was 80 respondents, consisting of two research objects, namely Kranggan Health Center and Pare Health Center. Determining the number of samples using the Non-probability approach through the saturated sample method, where the entire population is used as a sample. In this study using data analysis multiple linear regression test, t test and F test, the coefficient of determination. The results of the study show that work ability, organizational culture, and work discipline have an effect on employee performance partially or simultaneously. This conclusion is proven by the results of the t (partial) test which shows that work ability has a significant effect on employee performance by 0.048 <0.05, organizational culture has a significant effect on employee performance by 0.001 <0.05, and work discipline has a significant effect on employee performance by 0.016 <0.05. The results of the determination test show that the percentage of work ability, organizational culture, and work discipline simultaneously influences employee performance by 52.5%, while the remaining 47.5% is influenced by other variables outside of this study.Key words: Work Ability, Organizational Culture, Work Discipline, Employee Performance